Molecular phylogeography of East Asian Boea clarkeana (Gesneriaceae) in relation to habitat restriction. - Ying Wang; Kun Liu; De Bi; Shoubiao Zhou; Jianwen Shao (PLoS ONE)
Subfamily Cyrtandroideae (Gesneriaceae) comprises a broadly distributed group of rocky-slope herbs, with China being the center of its distributional range. The normal growth of many species within the family is particularly dependent on special habitats. Due to the paucity of molecular studies, very little is known regarding East Asian herb phylogeographic pattern. Here, we investigate the molecular phylogeography of Boea clarkeana Hemsl., a unique resurrection herb endemic to China, focusing on geographically restrictive effects of habitat distribution on evolutionary history. Variation in three chloroplast DNA (cpDNA) intergenic spacers (psbA-trnH, rps12-rpl20, and trnL-trnF), the ribosomal internal transcribed spacer (ITS) and simple sequence repeats in expressed sequence tags (EST-SSRs) was investigated across 18 populations to assess genetic diversity, genetic structure and historical dynamics. Genetic diversity was low within populations (cpDNA, hS = 0.03, πS×10(3) = 0.17; ITS, hS = 0.16, πS×10(3) = 0.43) but high for species (cpDNA, hT = 0.82, πT×10(3) = 3.12; ITS, hT = 0.88, πT×10(3) = 6.39); 76 alleles were detected in this highly inbred species (FIS = 0.22), with a significantly low average of 1.34 alleles per locus. No cpDNA or ITS haplotypes were shared between regions. Based on cpDNA results, the Mt. Huangshan-Tianmu and Mt. Qinling-Daba haplotypes are ancestral; these two regions represent potential refugia. Although no evidence of significant retreat-migration phenomena during glacial cycles was detected, interglacial range expansion from northern Mt. Qinling-Daba was identified (121,457 yr BP). Rapid agricultural growth caused bottlenecks in many populations, especially on Mt. Huang-Tianmu. Habitat restriction and fragmentation, weak seed and pollen dispersal abilities, and long-term isolation caused by human-induced or environmental changes are considered the main causes of extinction of several populations and low genetic diversity within populations and regions. These analyses clarify the effects of habitat restriction on B. clarkeana, representing an evolutionary reference for similar gesneriads, and enrich our understanding of the molecular phylogeography of East Asian rocky-slope herbs.